La valorisation des compétences de base sur le marché du travail français - Aline Branche-Seigeot (Recherches en Éducation)
In the human capital theory, individuals are paid according to their productivity, productivity depending on diploma or the number of years of education completed. But when certified education is devaluating, many consider skills, particularly basic skills, as a new filter. How are these basic skills valued on the french labour market? A lot of studies have been conducted on this topic (particularly in Anglo-Saxon countries), but not in France. This article attempts to determine, with a Heckman’s sample selection model, to what extent employment and wages can be explained by the level of literacy, numeracy and listening comprehension. Our method is informative because on the one hand it takes into account a possible selection bias in the estimation of wage equation and on the other hand, it enables to grasp the effects of basic skills in access to employment.